Гідрогеноліз ксилози до С2-С3 діолів на Cu-Cr2O3/Al2O3 каталізаторі - Horbaniuk, I.S.; Trachevskiy, V.V.; Brei , V.V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2025)
This study is dedicated to the continuous-flow hydrogenolysis of xylose 10 wt. % solutions in a methanol-water mixture to produce ethylene glycol and propylene glycol over Cu-Cr2O3/Al2O3 catalyst. A series of catalyst samples with varying CuO loadings (13–19 wt. %) were synthesized through wet impregnation of ?-Al2O3 support followed by heat treatment at 350 °C for 4 hours and later reduction of CuO by H2 to metallic copper. Complete reduction of CuO to metallic copper was confirmed by X-ray diffraction analysis of samples. To investigate the acid-base characteristics of obtained catalysts, desorption mass spectrometry was used. Catalytic experiments were conducted in a stainless steel flow reactor with a fixed catalyst bed (4 cm3, ~2.3 g) under conditions of 180 °C, 4.0 MPa H2 pressure, and a catalyst load of 1.6 mmol C5H10O5/gcat/h. According to product analysis using 13C NMR spectroscopy and gas chromatography, propylene glycol and ethylene glycol as main products, along with minor amounts of xylitol, glycerol, hydroxyacetone, and other by-products were identified. The 19Cu-Cr2O3/Al2O3 catalyst provides complete xylose conversion with productivities of 1.0 mmol/gcat/h for propylene glycol and 0.7 mmol/gcat/h for ethylene glycol. Lowering Cu content in Cu-Cr?O?/Al?O? catalyst resulted in decreasing its productivity. At 13 % Cu content, undesirable hydroxyacetone was observed. Noted, the catalyst exhibited consistent activity for 15 h in the methanol-water system, significantly exceeding the 8 h stability observed in 10 wt. % aqueous xylose solutions. This enhanced stability is attributed to improved hydrogen solubility and effective dissolution of intermediate products in the methanol-water mixture that prevents catalyst deactivation.